Implementation of the new WHO antenatal care model for a positive pregnancy experience: a monitoring framework - Özge Tunçalp; Samantha R Lattof; Allisyn C Moran; Theresa Diaz; Chandani Anoma Jayathilaka; Ann-Beth Moller; Nancy Kidula (BMJ Global Health)
Monitoring the implementation and impact of routine antenatal care (ANC), as described in the new World Health Organization (WHO) ANC model, requires indicators that go beyond the previously used global benchmark indicator of four or more ANC visits. To enable consistent monitoring of ANC content and care processes and to provide guidance to countries and health facilities, WHO developed an ANC monitoring framework. This framework builds on a conceptual framework for quality ANC and a scoping review of ANC indicators that mapped existing indicators related to recommendations in the new WHO ANC model. Based on the scoping review and following an iterative and consultative process, we developed a monitoring framework consisting of core indicators recommended for monitoring ANC recommendations in all settings, as well as a menu of additional measures. Finally, a research agenda highlights areas where ANC recommendations exist, but measures require further development. Nine core indicators can already be monitored globally and/or nationally, depending on the preferred data sources. Two core indicators (experience of care, ultrasound scan before 24 weeks) are included as placeholders requiring priority by the research agenda. Six context-specific indicators are appropriate for national and subnational monitoring in various settings based on specific guidance. Thirty-five additional indicators may be relevant and desirable for monitoring, depending on programme priorities. Monitoring implementation of the new WHO ANC model and the outcomes of routine ANC require greater attention to the measurement of ANC content and care processes as well as women’s experience of ANC.